Unleashing the green potential: Unraveling the power of environmental concerns in driving employees’ green behavior - Nhon Hoang Thanh; Bac Truong Cong (PLoS ONE, 2025)
This study investigates how environmental concerns influence employees’ green behavior within businesses, with a focus on the roles of attitude, green knowledge, and perceived behavioral control, underpinned by the Theory of Planned Behavior (TPB). Guided by TPB, this study develops a model where environmental concern impacts employee green behavior both directly and indirectly through its influence on attitudes, perceived behavioral control, and green knowledge. The study employed a structured survey of companies listed on the Vietnam Stock Exchange, targeting directors and senior managers between April and December 2021. A total of 407 valid responses were analyzed using structural equation modeling. The findings reveal that environmental concerns, attitudes, and perceived behavior control significantly influence employees’ green behavior. Both attitudes and perceived behavior control act as positive mediators in the relationship between environmental concern and employees’ green behavior. Additionally, the study highlights that the level of environmental consciousness is a crucial factor in shaping the connections between attitudes, perceived behavior control, and employee green behavior. These insights offer a novel perspective on the complex dynamics of environmental concerns in the corporate workplace, paving the way for the development of strategies that promote environmentally friendly behaviors within organizations.